Village Government Communication Patterns In Preventing Stunting In The Village Batu Gingging, Bangun Purba, District Deli Serdang - Zuhra, Fatimah; Simamora, Irma Yusriani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This research aims to know the communication patterns of the village government in preventing stunting in the village of Batu Gingging, Bangun Purba, districts of Deli Serdang. This study is a descriptive qualitative study, which uses data collection techniques through participant observations, semi-structured interviews and documentation. Data analysis techniques in this study by using the miles and huberman models, i.e. by performing data reduction, data presentation and verification. The results of this research showed that the village government played an important role in preventing stunting in the village of Batu Gingging, Bangun Purba, district of Deli Serdang. The communication pattern carried out by the Village Government is very important to increase public awareness and participation in stunting prevention. In the communication pattern, the Village Government carries out several activities such as socialization, training, coordination, provision of resources, encouraging public participation, and monitoring and evaluation